The role of histone H2Av variant replacement and histone H4 acetylation in the establishment of Drosophila heterochromatin. - Swaminathan, J.; Baxter, E.M.; Corces, V.G. (Genes & Development, 2005)
Activation and repression of transcription in eukaryotes involve changes in the chromatin fiber that can be accomplished by covalent modification of the histone tails or the replacement of the canonical histones with other variants. Here we show that the histone H2A variant of Drosophila melanogaster, H2Av, localizes to the centromeric heterochromatin, and it is recruited to an ectopic heterochromatin site formed by a transgene array. His2Av behaves genetically as a PcG gene and mutations in His2Av suppress position effect variegation (PEV), suggesting that this histone variant is required for euchromatic silencing and heterochromatin formation. His2Av mutants show reduced acetylation of histone H4 at Lys 12, decreased methylation of histone H3 at Lys 9, and a reduction in HP1 recruitment to the centromeric region. H2Av accumulation or histone H4 Lys 12 acetylation is not affected by mutations in Su(var)3-9 or Su(var)2-5. The results suggest an ordered cascade of events leading to the establishment of heterochromatin and requiring the recruitment of the histone H2Av variant followed by H4 Lys 12 acetylation as necessary steps before H3 Lys 9 methylation and HP1 recruitment can take place.